Perbandingan Fonologi Bahasa Indonesia dan Bahasa Prancis - Happy Ratu Ferdyani; Abim Sulistio Ramdan; Ridwan Hidayat (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2023)
This article discusses a comparison of phonology between Indonesian and French. Through comparative analysis, this article aims to highlight the similarities and differences in the sound systems of the two languages. In a theoretical study, this article discusses the sound systems of Indonesian and French separately, including consonants, vowels, word stress and intonation in both languages. The method used in this research is contrastive analysis, where the sound systems of the two languages ​​will be compared directly to highlight similarities and differences.